Membrane trafficking functions of the ANTH/ENTH/VHS domain‐containing proteins in plants. Issue 17 (30th May 2022) - Feng, Yihong; Hiwatashi, Takuma; Minamino, Naoki; Ebine, Kazuo; Ueda, Takashi
Abstract : Subcellular localization of proteins acting on the endomembrane system is primarily regulated via membrane trafficking. To obtain and maintain the correct protein composition of the plasma membrane and membrane‐bound organelles, the loading of selected cargos into transport vesicles is critically regulated at donor compartments by adaptor proteins binding to the donor membrane, the cargo molecules and the coat‐protein complexes, including the clathrin coat. The ANTH/ENTH/VHS domain‐containing protein superfamily generally comprises a structurally related ENTH, ANTH, or VHS domain in the N‐terminal region and a variable C‐terminal region, which is thought to act as an adaptor during transport vesicle formation. This protein family is involved in various plant processes, including pollen tube growth, abiotic stress response and development. In this review, we provide an overview of the recent findings on ANTH/ENTH/VHS domain‐containing proteins in plants. Abstract : AP180 N‐terminal homology (ANTH) domain‐containing PICALM proteins mediate endocytic and exocytic transport of plasma membrane proteins in plant cells.